The Al-Qur'an in The View of Western Scholars: Analysis of Orientalist Thoughts on the Study of the Al-Qur'an: Al-Qur`An Dalam Pandangan Sarjana Barat: Analisis Pemikiran Kaum Orientalis terhadap Studi Al-Qur`an - Nehru Millat Ahmad (Aqwal: Journal of Qur'an and Hadis Studies, 2024)
Background and Objectives: The study of Qur'ānic interpretation is an evolving field of scholarly inquiry that attracts scholars from around the world. This study aims to explore the contributions and approaches used by Western scholars in the study of the Qur'ān, and to see how changes in methodologies and perspectives in the interpretation of this sacred text affect its understanding and application in modern contexts. Methodology: Descriptive-analytical approach with library research method. The data sources used include books, journals, and scientific articles relevant to the theme of the study. Main Findings: Qur'anic studies continue to experience significant methodological variations, from criticism to the development of new methodologies. Hermeneutics and historical-critical approaches are the main methods used by Western scholars in understanding the Qur'an. The findings show that scriptural interpretation is always contextual and dynamic, influenced by social, cultural and political changes. Involvement: The contributions of Western scholars have significantly enriched Qur'anic studies through the use of innovative and critical methodologies. For instance, the application of the hermeneutic approach has deepened and contextualized the understanding of the Qur'anic text. Additionally, these contributions have introduced new methods that Muslim scholars can adopt to enhance their perspectives on interpreting the sacred text. Conclusion: The studies by Western scholars illustrate that interpreting these sacred texts remains pertinent to contemporary situations and can generate new ideas shaped by social, cultural contexts and academic methodologies. This research emphasizes the importance of inter-civilizational dialogue and openness to new approaches in studying sacred texts to achieve a more comprehensive and objective understanding.